ULAMA PERSIA DAN ULAMA NUSANTARA: Melihat Benang Merah Ide Pan Islamisme dan Implementasinya - M. Hasbi Amiruddin (Media Syari'ah, 2017)
Muslims have experienced the golden years, but then also had gone through a period of decline. Setbacks experienced by Muslims have occurred up to the breaking point, which is almost all Muslim countries had been colonized by the West. At the moment this is the bleak future global leaders later emerged, Jamaluddin Al-Afghani, called for reinforcing the unity of Muslims worldwide. This movement of ideas and then does look emerge in various Muslim countries. This is then assumed to have a common thread between Jamaluddin Al-Afghani who came from Persia with clerical movements in the archipelago.